2018
DOI: 10.1039/c8ob02250j
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and application of a highly branched, mechanism-based 2-deoxy-2-fluoro-oligosaccharide inhibitor ofendo-xyloglucanases

Abstract: Xyloglucan (XyG) is a complex polysaccharide that is ubiquitous and often abundant in the cell walls of terrestrial plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…102 Similarly, specifically engineered glycosynthase enzymes have been used to extend the nonreducing end of monosaccharide inhibitors to yield the corresponding disaccharide and trisaccharide inhibitors. 105 the other hand, we have previously been successful in stereoselectively 2-fluorinating a complex xyloglucan heptasaccharide (Xyl 3 Glc 4 , "XXXG") glycal with Selectfluor in the synthesis of an endo-xyloglucanase inhibitor, 21 which avoided tedious stepwise oligosaccharide construction. 106,107 Yet, prior to the present study, the use of Selectfluor on glycals containing β(1,3) glycosidic linkages had not been explored.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…102 Similarly, specifically engineered glycosynthase enzymes have been used to extend the nonreducing end of monosaccharide inhibitors to yield the corresponding disaccharide and trisaccharide inhibitors. 105 the other hand, we have previously been successful in stereoselectively 2-fluorinating a complex xyloglucan heptasaccharide (Xyl 3 Glc 4 , "XXXG") glycal with Selectfluor in the synthesis of an endo-xyloglucanase inhibitor, 21 which avoided tedious stepwise oligosaccharide construction. 106,107 Yet, prior to the present study, the use of Selectfluor on glycals containing β(1,3) glycosidic linkages had not been explored.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Notably, in our previous work, the reaction of a highly branched xyloglucan heptasaccharide glycal afforded exclusively the gluco epimer with an anomeric α/β mixture (as confirmed by 19 F nuclear magnetic resonance (NMR) spectroscopy). 21 Since we were unfortunately unable to bias the diastereoselectivity of fluorination here, the reactions of glycals 9 and 10 with Selectfluor were scaled-up using acetone/water (5:1) as a convenient solvent system to achieve moderate yields of diastereomeric mixtures. 19 F NMR spectra indicated that the diastereomeric ratios were similar to those observed in the small-scale reactions (11,Figure S27 in the Supporting Information; 12, Figure S28 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations